PENINGKATAN KUALITAS LIMBAH KULIT SINGKONG MELALUI PENAMBAHAN ASAM PROPIONAT SEBAGAI BAHAN BAKU PAKAN TERNAK - Akhadiarto, S. (BPPT)
Feed represent especial factors of animal husbandry because owning biggest expense from production cost. Feed effi ciency must be done to increase earnings. One of effort for the matter of that is look for alternative of raw material feed of cheaper livestock that is cassava peels. Cassava peels represent waste product from cassava industry with amount 1,998 million ton in the year 2006 in Indonesia (10 percentage of corm of yielded cassava). As constraint is its amount is which have the fl uctuation so that need depository effort of cassava peels. This research aim to know infl uence of use propionic acid as preservative to quality of nutrient of cassava peels. A period of depository observed too for its quality. Research conducted by during six-month in feed industrial laboratory of indicate that addition of 0.3% propionic acids and depository period infl uence quality of nutrient of cassava peels manifestly (P 0.05). Addition of 0.3% propionic acid gratuity not yet able to pursue growth of microorganism during depository. Growth of mould during depository infl uence to descend of water percentage, organics substance, protein, digesting of organic substance and digesting of dry substance.Key words : cassava pells, waste, propionic acids, nutrient.